2019
DOI: 10.1109/tpwrs.2018.2863042
|View full text |Cite
|
Sign up to set email alerts
|

Robust Power Flow and Three-Phase Power Flow Analyses

Abstract: Robust simulation is essential for reliable operation and planning of transmission and distribution power grids. At present, disparate methods exist for steady-state analysis of the transmission (power flow) and distribution power grid (threephase power flow). Due to the non-linear nature of the problem, it is difficult for alternating current (AC) power flow and threephase power flow analyses to ensure convergence to the correct physical solution, particularly from arbitrary initial conditions, or when evalua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 27 publications
1
93
0
Order By: Relevance
“…Using the circuit heuristics, we are able to solve large and complex power systems robustly [17]. We further extend these properties to frequency dependent proposed formulation as shown in Figure 3.…”
Section: Scalabilitymentioning
confidence: 94%
“…Using the circuit heuristics, we are able to solve large and complex power systems robustly [17]. We further extend these properties to frequency dependent proposed formulation as shown in Figure 3.…”
Section: Scalabilitymentioning
confidence: 94%
“…One of the circuit simulation methods limits the Newton-Raphson (NR) step to avoid leading the solution to a space that may cause divergence or oscillations. In [13], we demonstrated that damping the step size of each element based on the physical properties results in better convergence of the solver. While limiting the NR step can improve convergence, limiting by itself does not guarantee that the solution represents a physically stable dispatch.…”
Section: A Current-voltage Approach To Power Flow Analysismentioning
confidence: 97%
“…Current-voltage (I-V) based formulations have been explored in the past for performing power flow and three-phase power flow analyses [13]- [16]. Amongst these approaches, a recently introduced equivalent circuit approach [13] maps the different network models of the grid (e.g. PV, PQ, etc.)…”
Section: A Current-voltage Approach To Power Flow Analysismentioning
confidence: 99%
See 2 more Smart Citations